Validity and reliability of the Turkish version of the COPD exercise self‐regulatory efficacy scale. (18th December 2019) - Ünal Aslan, Kevser Sevgi; Çetinkaya, Funda
Abstract: Introduction: The concept of self‐efficacy in chronic obstructive pulmonary disease (COPD) and the development of self‐efficacy in individuals are extremely significant. Increasing the self‐efficacy level in individuals with COPD will contribute to the effective management of symptoms. Moreover, exercise is essential in COPD management and nursing care. Objectives: This study aimed to evaluate the results of the validity and reliability study of the Turkish version of the COPD Exercise Self‐Regulatory Efficacy Scale (Ex‐SRES) developed by Davis et al. Methods: This is a methodological study conducted with 160 patients diagnosed with COPD. Data were collected using the Personal Information Form and COPD Ex‐SRES. Moreover, the Cronbach's α value was calculated, and the test‐retest reliability was performed for reliability analysis. Results: The item total correlation scores of the Turkish version were between 0.608 and 0.853 points. The total score correlation coefficients of all the items in the scale were over 0.30. In this respect, the item total correlation values of the Turkish version of the Ex‐SRES were at an appropriate level of reliability. In addition, the total Cronbach's α coefficient of the scale was calculated as 0.96. Conclusion: The Turkish version of the Ex‐SRES was found to have high validity and reliability and to be a precise tool that specifically measures exercise self‐efficacy in the COPD patient group.